Initial, long-term, and durable responses to terazosin, placebo, or other therapies for chronic prostatitis/chronic pelvic pain syndrome - Cheah, Phaik Yeong; Liong, Men Long; Yuen, Kah Hay; Teh, Chu Leong; Khor, Timothy; Yang, Jin Rong; Yap, Hin Wai; Krieger, John N. (Urology (Ridgewood, N.J.), 2004)
To evaluate the initial, long-term, and durable response rates to terazosin, placebo, or other therapies in patients with chronic prostatitis/chronic pelvic pain syndrome. A total of 100 subjects, aged 20 to 50 years, who met the National Institutes of Health criteria for chronic prostatitis/chronic pelvic pain syndrome and had not previously been treated with alpha-blockers, were entered in a 14-week, double-blind comparison of terazosin or placebo therapy. Nonresponders and responders with subsequent relapse were treated with terazosin or other medications (open label). The criterion for response was a score of 0 to 2 on the National Institutes of Health Chronic Prostatitis Symptom Index quality-of-life item. The initial response was evaluated at week 14, and the long-term response was evaluated after a median of 38 weeks (range 34 to 42), regardless of any additional treatment. A durable response was defined as an initial response without additional treatment. Of the 43 patients in the terazosin group, 24 (56%) had an initial response compared with 14 (33%) of 43 subjects in the placebo group (P = 0.03). Long-term responses were noted in 23 (56%) of 41 assessable subjects treated with terazosin initially compared with 12 (32%) of 38 assessable subjects treated with placebo (P = 0.03). Of the nonresponders and initial responders with relapse, 7 (41%) of 17 subjects responded to terazosin compared with 7 (21%) of 34 given other treatment (P = 0.12). Durable responses occurred in 18 (44%) of the 41 assessable patients treated initially with terazosin and in 6 (16%) of 38 treated initially with placebo (P = 0.01). Patients treated with terazosin were more likely to have initial, long-term, and durable responses than those treated with placebo.